Les pèlerinages dans les régions dévastées du nord de la France organisés par la Compagnie du chemin de fer du Nord au lendemain de la Première Guerre mondiale - Gersende Piernas (In Situ)
As early as 1919, the Compagnie du chemin de fer du Nord, the North railway company, organised regular circuits to visit the French and British battlefields of the First World War, departing from Paris or other large towns in the north. These circuits, with aspects that were political, economic, tourist and historic, were described as ‘pilgrimages’, to counter the propaganda of the now defeated enemy which had denied the reality of its destructions. The organisation of these trips demonstrated a will to share the history of the recent conflict with a large public, contributing to the development of myths surrounding the war, its protagonists such as the ‘Poilu’, the French infantryman, and the debt to the allied forces of liberation.